2021
DOI: 10.1021/acs.energyfuels.1c00588
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics Investigation of Geochemical Alterations in Marcellus Shale Using Reactive Core-Floods

Abstract: The interaction of reactive fracture fluid with host shale and formation water plays an important role on fractured reservoir productivity. This study explores the prominent impacts of shale−fluid reactions on flow properties using representative core-flood experiments under confining stress. Alteration of shale is monitored using time-lapse X-ray computed tomography (CT), microCT (μCT) of samples preand post-reaction, and scanning electron microscopy (SEM). The imaging approach is multiscale from nm's to cm's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…This stimulation, which is spearheaded by highly oxic acidic fluid, generates both conductive fractures and a more permeable matrix/fracture interface, allowing the release of hydrocarbons from the shale interior into the propped advective conduits. , A cascade of physicochemical interactions subsequently unfold between low-pH HFF and shale rock, creating coupled mineral dissolution and precipitation reactions, along with wettability alteration, shale softening, and fines migration . These effects ultimately dictate fracture conductivity and the lifespan of productivity for a given well. , Multiple studies have focused on the chemical reactions occurring at the shale/HFF interface, with the general consensus that pyrite readily oxidizes and carbonates are dissolved creating pore space on the fracture surface. The reactions that occur are highly dependent on the shale mineralogy, specifically the carbonate and clay content, and the HFF composition. , Most of these experiments involve immersion-type batch reaction systems, ,,, where reactive brine is allowed to interact with a shale sample subject to diffusive solute transport in an enclosed chamber for an extended period of time, mimicking the shut-in period during the hydraulic fracturing operation. A limited number of studies have been conducted under advective flow conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This stimulation, which is spearheaded by highly oxic acidic fluid, generates both conductive fractures and a more permeable matrix/fracture interface, allowing the release of hydrocarbons from the shale interior into the propped advective conduits. , A cascade of physicochemical interactions subsequently unfold between low-pH HFF and shale rock, creating coupled mineral dissolution and precipitation reactions, along with wettability alteration, shale softening, and fines migration . These effects ultimately dictate fracture conductivity and the lifespan of productivity for a given well. , Multiple studies have focused on the chemical reactions occurring at the shale/HFF interface, with the general consensus that pyrite readily oxidizes and carbonates are dissolved creating pore space on the fracture surface. The reactions that occur are highly dependent on the shale mineralogy, specifically the carbonate and clay content, and the HFF composition. , Most of these experiments involve immersion-type batch reaction systems, ,,, where reactive brine is allowed to interact with a shale sample subject to diffusive solute transport in an enclosed chamber for an extended period of time, mimicking the shut-in period during the hydraulic fracturing operation. A limited number of studies have been conducted under advective flow conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xiong et al injected brine through fractured Wolfcamp shale and reported evidence of a more pronounced dissolution in carbonate-rich shale, compared to the clay-rich shale sample on the fracture surfaces. Similarly, Gundogar et al saw carbonate-rich Marcellus samples exhibit evidence of washout and etching on the rock surface, which was absent for the low-carbonate Marcellus samples. Both of these experiments were conducted over long flow durations (>1 week), at slow flow rates (>20 μL/min), and at temperatures and pressures representative of subsurface conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior static batch experiments revealed that the dissolution of pyrite and carbonate minerals occurred rapidly, releasing metal contaminants and generating porosity . The chemically altered reaction front extends from the shale–fluid interface into the rock matrix on a micrometer to millimeter scale. ,, The thickness of the reaction front and permeability of the shale cores can provide key insights for fluid penetration into the shale matrix …”
Section: Resultsmentioning
confidence: 99%
“…36,37 Pyrite, in particular, readily oxidizes to Fe(III) and, depending on the solution pH, rapidly precipitates as Fe (oxyhydr)oxides. 6,10,14,38 Because solution pH has a strong influence on the rate of Fe(II) oxidation, the carbonate content of the rock can also influence this process. Jew et al 39 observed that in Marcellus shales with a low carbonate content (12% calcite, 1% dolomite), dissolved Fe(II) remains in solution for a significant amount of time, allowing transport to occur prior to oxidation and precipitation.…”
Section: ■ Introductionmentioning
confidence: 99%